Probing biomolecular structures and dynamics of single molecules using in-gel alternating-laser excitation. - Santoso, Y; Kapanidis, A (2009)
Gel electrophoresis is a standard biochemical technique used for separating biomolecules on the basis of size and charge. Despite the use of gels in early single-molecule experiments, gel electrophoresis has not been widely adopted for single-molecule fluorescence spectroscopy. We present a novel method that combines gel electrophoresis and single-molecule fluorescence spectroscopy to simultaneously purify and analyze biomolecules in a gel matrix. Our method, in-gel alternating-laser excitation (ALEX), uses nondenaturing gels to purify biomolecular complexes of interest from free components, aggregates, and nonspecific complexes. The gel matrix also slows down translational diffusion of molecules, giving rise to long, high-resolution time traces without surface immobilization, which allow extended observations of conformational dynamics in a biologically friendly environment. We demonstrated the compatibility of this method with different types of single molecule spectroscopy techniques, including confocal detection and fluorescence-correlation spectroscopy. We demonstrated that in-gel ALEX can be used to study conformational dynamics at the millisecond time scale; by studying a DNA hairpin in gels, we directly observed fluorescence fluctuations due to conformational interconversion between folded and unfolded states. Our method is amenable to the addition of small molecules that can alter the equilibrium and dynamic properties of the system. In-gel ALEX will be a versatile tool for studying structures and dynamics of complex biomolecules and their assemblies.